The GCC Banking Sector : Topography and Analysis - Khamis, May.; Al-Hassan, Abdullah; Oulidi, Nada. (Washington, D.C. : International Monetary Fund, 2010)
In this paper, we analyze the evolution of the Gulf Cooperation Council (GCC) banking sectors in the six member countries including ownership, concentration, cross-border linkages, balance sheet exposures and risks, recent trends in credit growth, and financial soundness. We identify risks to the banking sector's financial stability in the context of the current global crisis and their mitigating factors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet